Integrated impact time guidance and control against non-maneuvering targets. (December 2022) - Patil, Aditya; Kumar, Shashi Ranjan
This paper proposes integrated guidance and control for skid-to-turn cruciform canard-controlled interceptors for controlling impact time along with interception of non-maneuvering targets. This approach circumvents the possible difficulties associated with designing guidance and control subsystems independently. An interceptor control surface deflection for achieving appropriate lateral acceleration to achieve the guidance objectives are derived using sliding-mode control considering nonlinear engagement dynamics, thereby remaining effective even for engagement with large initial heading errors. The switching surface is chosen to be a function of time-to-go and its rate with different time-to-go estimates against stationary and moving targets. The time-to-go estimate for stationary target accounts for the heading angle errors, while that for constant velocity target provides an exact value. Unlike many of the existing strategies, the proposed approaches enable the interceptor to achieve an impact time, even less than its initial estimates. The efficacy of the proposed guidance strategies is validated through numerical simulations for various initial engagement geometries. Furthermore, the performance of the proposed integrated guidance and control approach is also compared with the separate design of guidance and control subsystems, and shown to be superior.